1980
DOI: 10.1007/bf00141456
|View full text |Cite
|
Sign up to set email alerts
|

Ocular penetration of β-adrenergic blocking agents. An experimental study with atenolol, metoprolol, timolol and propranolol

Abstract: A comparison was made between the ocular penetration of topically applied 14C-atenolol, 14C-timolol, 14C-propranolol and 3H-metoprolol by means of liquid scintillation counting. Only one eye was treated, the fellow eye served as a control. Blood plasma levels were measured as well. We could detect a relationship between the ocular penetration and the degree of lipophilicity of the drugs used, as was to be expected. Drugs with a higher degree of lipophilicity penetrated more readily into the eye, whereas they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Since there is a positive relationship between ocular penetration and lipophilicity of the drug used this can be a pharmacokinetic feature in favour of timolol (Ros et al 1979). How important this aspect is was demonstrated with a pro-drug version of Nadolol, the DiacetateNadolol.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since there is a positive relationship between ocular penetration and lipophilicity of the drug used this can be a pharmacokinetic feature in favour of timolol (Ros et al 1979). How important this aspect is was demonstrated with a pro-drug version of Nadolol, the DiacetateNadolol.…”
Section: Discussionmentioning
confidence: 96%
“…The virgin eye in terms of betablockers is very sensitive towards this group of compounds, so even a very weak betablocker can give an excellent initial response which however may wear off within days or weeks. Since there is a positive relationship between ocular penetration and lipophilicity of the drug used this can be a pharmacokinetic feature in favour of timolol (Ros et al 1979). How important this aspect is was demonstrated with a pro-drug version of Nadolol, the Diacetate-Nadolol.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al 80 compared the penetration of three b-blockers, bufuralol, timolol and acebutolol, into aqueous humor. Ros et al 81 also investigated the drug exposure of four b-blockers: atenolol, timolol, propranolol, and metoprolol. Both studies revealed that timolol showed higher AUC values than the more lipophilic compounds bufuralol and propranolol.…”
Section: B-blockermentioning
confidence: 98%
“…Both studies revealed that timolol showed higher AUC values than the more lipophilic compounds bufuralol and propranolol. 80,81 The lipophilic nature of these drugs led to the wide tissue distribution and lowered the aqueous humor drug levels. The less IOP reducing efficacy of propranolol relative to timolol may be due to the low unbound fraction caused by high lipophilicity.…”
Section: B-blockermentioning
confidence: 99%
“…Beta-blockers, when applied as an eye drop, are useful pharmacological agents in treating elevated intraocular pressure associated with glaucoma [1]. Beta-blockers are also commonly used as markers to study the influence of drug lipophilicity on permeability of various tissues because a series of beta-blockers are available with a wide range of lipophilicity (log P ranging from −1.0 to 3.0) and similar molecular weights (∼300) and pK a s (∼9.2) [2,3].…”
Section: Introductionmentioning
confidence: 99%